Hydrochemical study in surface waters of Barreiro, Araxá City, Minas Gerais State, Brazil - Mancini, Luis Henrique [UNESP]; Bonotto, Daniel Marcos [UNESP] (My University, 2014)
The chemical evolution of the Earths surface and, consequently, of the hydrographic basins, is controlled by several factors, among which are the interaction of rainwaters, the atmosphere and the continental crust. Different climatic conditions affect the denudation, chemical weathering and physical erosion in hydrographic basins. The present and future design of the hydrographic basins is affected by chemical weathering processes and such information has been increasingly used by decision makers engaged in the management of our river basin systems. A lot of factors have been applied in models that utilize the concentrations of constituents like sodium, calcium, potassium, magnesium and total dissolved solids for estimating the chemical weathering fluxes taking place in the drainage basins. On the other hand, the population growth in all countries has caused an increased concern on the quantity and quality of the water resources in hydrographic basins. Well-defined anthropogenic inputs and/or pollution from diffuse source loads have commonly affected the chemistry of water bodies, requiring special attention by people involved in the river basin management. This chapter reports the results of a hydrochemical study held at the Barreiro hydrographic basin, Araxá city, Minas Gerais State, Brazil. The surface water quality in the site is not only affected by geogenic inputs but also by anthropogenic sources that are mainly coupled to activities involving the mining and production of fertilizers, which take place in alkaline rocks belonging to the geological formations of the region.